Proceso de ASC - CONEXION ENTRE ESTACION DE TIERRA Y UAVS PARA USOS AGRONOMICOS Y/O SOCIALES (2020)
With this project, the use of the long-range ground station (500 km), located at the EAFIT Llanogrande headquarters, for agronomic and social applications was proposed. This station is in the start-up phase with the 2019 Applied Electromagnetism Seedbed (SEMA) project underway. Taking advantage of the payload capacity of an unmanned aerial vehicle (UAV) and the transmission range capacity of the base, activities in the agricultural sector can be carried out such as irrigation, fumigation and crop sensing among other applications, in addition to its possible use in humanitarian aid by having greater access through UAVs to places that cannot be easily accessed to transport objects and aid. Additionally, the proposal could very well be included as a topic of study in the recent undergraduate degree in agronomic engineering created at the University.